Vasculitis on brain angiography is not always vasculitis: intravascular large B-cell lymphoma mimicking central nervous system vasculitis. Issue 8 (26th August 2019) - Rayfield, Corbin; Mertz, Lester; Kelemen, Katalin; Aslam, Fawad
Abstract : A 68-year-old man, with a history of non-Hodgkin's lymphoma in remission, was admitted for homonymous hemianopsia, headaches and subacute progressive cognitive decline. Imaging revealed brain infarcts and angiography suggested vasculitis. A brain biopsy, however, revealed an intravascular large B-cell lymphoma (IVLBL). Central nervous system (CNS) vasculitis and IVLBL of the brain are extremely rare diseases that can have an almost identical clinical presentation. Angiographic findings are very similar but usually are reported as compatible with vasculitis. Brain biopsy or a random skin biopsy are crucial in diagnosing IVLBL as the accuracy of angiographic findings for CNS vasculitis is low.